Special Issue on Biowaste Treatment and Valorization - Carlos Rico De La Hera (Applied Sciences, 2022)
Biowaste has been defined as “Biodegradable waste from gardens and parks, food and kitchen waste from homes, restaurants, collective catering services and retail establishments, and comparable waste from food processing plants” (Directive (2008)/98/EC (EC—European Commission, 2008) [...]